A Recommendation System for Hotel in Bali Using Case Based Reasoning Method - Prashanti, Ni Putu Vidya Vira; Astawa, I Gede Santi (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 10 No 1 (2021): JELIKU Volume 10 No 1, Agustus 2021DO - 10.24843/JLK.2021.v10.i01.p02, 2021)
When on vacation, one of the essential amenities that is needed is the availability of accommodation such as hotel. One of the areas that become a holiday destination is the island of Bali. Being one of the tourist destinations of course many lodgings available in Bali with various facilities offered. The problem facing tourists is when choosing the right lodging that suits your wishes or needs, so in this study will be built a hotel recommendation system in Bali. The purpose of this research is to assist tourists in choosing the right hotel. The study used 78 hotel data sourced from the agoda.com. The methods used in this study are Case Based Reasoning and K-Nearest Neighbor.  The result of this study is that the hotel recommendation system in Bali has managed to provide hotel selection recommendations based on 14 features namely district, hotel class, room type, and availability of facilities such as breakfast, swimming pool, television, gym, air conditioner, scenery, and nightly stay price. Based on black box testing, it is obtained the result that the hotel recommendation system in Bali can function properly.